Theoretical analysis of type II dent pipe under external force. (July 2019) - Wu, Ying; Li, Linya
Abstract: In-service pipelines are often subject to external disturbances that produce dent defects, and the presence of dent defects often affects the pipeline's ultimate bearing capacity. This paper analyzes the equilibrium state of dent pipelines under external force for in-service pipelines with type II dent defects. A simplified calculation model for the shell is established through a series of assumptions and simplifications. Firstly, the pipe ring is crushed and analyzed to obtain the crushing power of the pipe ring, and then the pipe generator is subjected to deformation analysis to obtain the generator dissipating power. According to the principle of virtual work, the relationship between the external force power and the internal power dissipation power in equilibrium state is obtained. Under the condition of internal pressure, the type II dent defect is analyzed, and the relationship between the external force and the depth of the dent defect and its corresponding analytical expression are obtained. Under the condition of no internal pressure, the dent defect under different constraints is analyzed, and the analytical expression of the applied load under different constraints is obtained.